Via Giostra Vecchia: architecture and urban spaces in the old center of Cosenza - Aldo De Sanctis; Antonio Lio; Antonio Agostino Zappani (Disegnare con)
The study on via Giostra Vecchia in the old town of Cosenza constitutes an occasion for the analysis of the city, considering both the single buildings (with their technical-constructive, formal geometrical, deterioration properties) as well as the urban space intended as the “material” of the city, able to  contribute to determining its value. The restitutions of survey we propose have the objective of presenting with evidence both the architectural features of the buildings as well as the relationship between buildings and the urban space. They are complex restitutions of survey, realized with the combination of more drawings, necessary to out together for analysis and knowledge, homogeneous data on the issues mentioned above.